Surgimiento, evolución y consolidación del Derecho del Trabajo - Boza Pro, Guillermo (2014)
Labor Law arose from the need to provide protection  to  the  objectively weak part of the employment relationship: The  worker. However, how did Labor Law originated and inwhich way did it acquire its protective nature? In this article, the author presents a comprehensive history of the origins of Labor Law, the various stages it went through and even its arrival to Peru, as well as the challenges it currently faces.